Learning Strategies Used By Twelfth Year Students To Upgrade Their English For Facing National Examination Of SMK Muhammadiyah 1 Sukoharjo Academic Year 2015-2016 - Choiriyah, Irin Manila, Aryati Prasetyarini, S.Pd, M.Pd, Siti Fatimah, S. Pd, M. Hum (2016)
This research aims at finding out and describing the learning strategies used by twelfth year students to upgrade their English for facing national examination of SMK Muhammadiyah 1 Sukoharjo. The type of this research is descriptive qualitative which aims to describe the strategies applied by the twelfth year students for facing national examination. The methods of collecting the data are observation, interview, and documentation. The data are taken from the subject of the research in the form of field notes, interview, and document. The result of the research shows that the twelfth year students use kinds of learning strategies based on O'Malley and Chamot: meta-cognitive, cognitive, and social-affective strategies. The first subject is AM. He uses 10 strategies which consist of 4 in meta-cognitive, 4 in cognitive, 2 in social-affective. The second subject is AA. She uses 9 strategies which consist of 4 in meta-cognitive, 3 in cognitive. The third subject is SF uses 10 strategies which consist of 5 in meta-cognitive, 4 in cognitive, 1 in social-affective. The fourth subject is WIN. He uses 6 strategies which consist of 2 in meta-cognitive, 3 in cognitive, 1 in social-affective. The students of software engineering who has higher mark apply more strategies than students of motorcycle engineering. Thus, the researcher can conclude that learning strategies used by software engineering are more effective to help the students for facing national examination. In specific, those are strategies used by students of software engineering which did not use by students of motorcycle engineering namely, note taking strategy and cooperation strategy.